Application of Khutuatut Tadries Al Mufashsholah in Maharah Al-Kitabah Learning for Semester II A IDIA Prenduan Students - Izzat Amini; Nurhikmah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The use of strategies in learning is one of the supports for achieving the desired goals. To create an effective classroom atmosphere, a teacher is required to use learning strategies that are active, fun and do not seem boring to students. One of these strategies is khutwatut tadris al-mufassolah which was prepared by KH. Muhammad Idris Djauhari. This learning step uses Herbart's theory and was perfected by KH. Muhammad Idris Djauhari in studying the Maharah Kitabah. This strategy makes students more active during learning. This research aims to determine the process of learning Maharatul Kitabah and the application of Khutwatut Tadries Al-Mufashsholah as well as the factors that support and hinder the application of Khutwatut Tadries Al-Mufashsholah in learning Maharatul Kitabah among second semester students at Ma'had IDIA Prenduan. This research uses a qualitative approach and collects data using observation, interviews and documentation. The data analysis techniques used are condensation, data presentation and drawing conclusions. Meanwhile, the analysis of the validity of the data used is triangulation. The results of this research show that the Maharatul Kitabah learning process for IDIA Prenduan second semester students was carried out with 5 activity stages, namely opening, presentation, association, conclusion, and application. However, in its implementation there are also several factors that hinder it, namely lack of mastery of mufrodat, no special teacher guidance, no lesson plans. Meanwhile, the factors that support the implementation of khutwatut tadries al-mufashsholah are the student's activeness, the teacher's clear makhorijul letters, the teacher's pleasant demeanor.